(3GdSjGSGJ GdfbOjI h GdeGdjI h EOGQI Shb GdGhQGb GdeGdjIs - (3YHGS cGXe(B, (3GdOYejs ((3YeGf(B:s (3OGQ UaGA(B,s, 2010)
(3WHjYI GdSjGSI GdfbOjI hGdSjGSGJ GdeGdjI h OhQgG aj GdeOGQS GdGbJUGOjI GdSjGSGJ GdfbOjI h GdeGdjI aj EWGQ GdGbJUGO Gdcdj , GdJQcjH GdHfjhj ddCShGb GdeGdjI , GdeDTQGJ GdQFjSI dCOGA CShGb GdChQGb GdeGdjI h WQGFb HfGFgG , GdShb GdeGdjI GdcahA h GdeMaXI GdGSJKeGQjI , GdSjGSI GdfbOjI h GdeGdjI aj eUQ eDTQGJ GOGA Shbj eUQ hfjhjhQc ddChQGb GdeGdjI (B1990-2006 (3, JMOjO GdeJZjQGJ h HfGA GdfeGPL GdbjGSjI , JbOjQ h JMdjd CKQ GdSjGSGJ GdfbOjI h GdeGdjI aj eDTQGJ COGA Shb eUQ h GdhdGjGJ GdeJMOI ddChQGb GdeGdjI, fJGFL JMdjd CKQ GdSjGSGJ GdfbOjI h GdeGdjI aj eDTQGJCOGA GdShbjf (B((3OQGSI ebGQfI (B).s
(3eQGLY U(B.399 (3; agQS LOGhd U(B.12 (3;agQS GTcGd U(B.14 (3;agQS edGMb U(B.19s
Keywords: (3GdGOGQI GdeGdjIs; (3GdGbJUGO GdeGdjs; (3GdSjGSI GdeGdjIs; (3GdSjGSI GdfbOjIs